ME to WE Social Entrepreneurship: A Wolf in Sheep’s Clothing - Karsgaard, Carrie; Shultz, Lynette (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2022)
The story of the WE enterprise, also known as ME to WE or WE Charity, presents us with a cautionary tale for teachers who welcome social enterprise into schools as a way of bringing community engagement and social justice into their educational programs. Our paper is a cautionary tale that, like all such tales, opens with the statement of a warning about social entrepreneurship in schools. As the narrative unfolds, this warning is disregarded, and the violator ultimately experiences an unpleasant fate. Using the large-scale data available on Instagram, this paper reveals in detail how WE represented itself, how others perceived it, and how it worked in and with schools to achieve its corporate goals. We conclude the tale by discussing how, by delinking education from corporate interests, schools may serve equity and the public good instead of creating brand fanatics in the service of elite interests.